2021
DOI: 10.1021/acs.jpclett.1c02542
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Highly Stable and Wavelength-Tunable Tin Based Perovskite Materials with Enhanced Quantum Yield via the Cation Transformation Reaction

Abstract: Metal halide perovskites have attracted great attention for their superior light energy conversion applications. Herein, we demonstrated a facile synthesis of zero-dimensional Sn2+ perovskite Cs4–x M x SnBr6(M = K+ and Rb+) material through the cation transformation reaction at room temperature. Cs4SnBr6 NCs was mixed with pure metal bromide salts (KBr and RbBr) via the mechanochemical process to successfully synthesize Cs4–x M x SnBr6 perovskite where transformation of Cs to mixed Cs/Rb and mixed Cs/K was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Rare-earth-based or doped compounds are widely used in various application fields such as phosphors, sensors, display devices, anticounterfeiting, and cryogenic refrigerants, due to their superior optical and magnetic properties. Recently, layered rare-earth hydroxides (LREHs) with a general formula of RE 8 (OH) 20 A 4 · n H 2 O (RE: rare-earth ion; A: intercalated anion) have emerged as an important family of anion-exchangeable host materials and attracted wide attention. LREHs consist of positively charged host layers and interlayer moieties such as chloride (Cl – ) and nitrate (NO 3 – ) anions. The positively charged host is derived from a partial replacement of hydroxyl groups (OH – ) by water molecules (H 2 O) in the 8- and 9-coordination of RE 3+ .…”
mentioning
confidence: 99%
“…Rare-earth-based or doped compounds are widely used in various application fields such as phosphors, sensors, display devices, anticounterfeiting, and cryogenic refrigerants, due to their superior optical and magnetic properties. Recently, layered rare-earth hydroxides (LREHs) with a general formula of RE 8 (OH) 20 A 4 · n H 2 O (RE: rare-earth ion; A: intercalated anion) have emerged as an important family of anion-exchangeable host materials and attracted wide attention. LREHs consist of positively charged host layers and interlayer moieties such as chloride (Cl – ) and nitrate (NO 3 – ) anions. The positively charged host is derived from a partial replacement of hydroxyl groups (OH – ) by water molecules (H 2 O) in the 8- and 9-coordination of RE 3+ .…”
mentioning
confidence: 99%
“…To investigate the intrinsic PL nature of Cs 4 SnBr 6 , time‐resolved PL spectra were recorded under an excitation of 365 nm (Figure 2c), wherein, original Cs 4 SnBr 6 ‐SnBr 2 exhibited a monoexponential decay with an average lifetime of 506 ns. For Cs 4 SnBr 6 ‐SnF 2 crystals, it was observed that the lifetime increased to 741 ns, indicating that the prolonged lifetime implied the passivation of defects and the increase of radiation recombination [24, 27] . For the Sn‐based perovskite, the oxidation of Sn 2+ may generate Sn vacancies, which may serve as defect states to induce serious non‐radiative recombination.…”
Section: Resultsmentioning
confidence: 99%
“…The broad‐band, strongly Stokes‐shifted emission (Figure 2a and Figure S8), and relatively long radiative lifetimes indicated that the PL emission of Cs 4 SnBr 6 originates from the radiative process of self‐trapped excitons (STEs) recombination (Figure 2g) [18–27] . In zero‐dimensional perovskite, once carriers are photogenerated, excited‐state electrons will be rapidly self‐trapped by the distorted lattice and then release energy by recombination processes, which is the typical light‐emitting mechanism of STEs [28, 29] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng et al. demonstrated that the A-site cation of lead-free Cs 4 SnBr 6 NCs could be partially substituted via a balling process at room temperature while the pristine Cs 4 SnBr 6 NCs were fabricated using an HI method ( Meng et al., 2021 ). By mixing the Cs 4 SnBr 6 NCs with pure metal bromide salts (KBr and RbBr), the transformation of Cs to mixed Cs/Rb and mixed Cs/K could be readily achieved.…”
Section: Synthesis Of Perovskite Nanocrystalsmentioning
confidence: 99%